RANCANG BANGUN SISTEM ABSENSI DENGAN RFID BERBASIS IoT PT. UMBI TEKNOLOGI INDONESIA - Gabriel Ardana; Nurchim; Bondan Wahyu Pamekas (Fakultas Teknik Universitas Pasifik Morotai, 2024)
In today's digital era, information technology automation plays a crucial role in enhancing operational efficiency across various sectors, including education and industry. This article discusses the design and development of an attendance system based on the Internet of Things (IoT) utilizing Radio Frequency Identification (RFID) technology. The system is designed to replace manual attendance methods, which are often time-consuming and prone to human error. The proposed system consists of RFID hardware connected to an IoT network to collect attendance data in real-time. The data is then sent to a server via the internet and can be accessed through a website. This system enables instant attendance monitoring and automatic reporting with greater accuracy and efficiency. Testing results show that the RFID and IoT-based attendance system can improve the accuracy and speed of attendance recording. Therefore, the implementation of RFID and IoT technology in this attendance system can significantly contribute to enhancing the efficiency and accuracy of attendance management.